Gabapentinoid Use Is Associated With Reduced Occurrence of Hyperactive Delirium in Older Cancer Patients Undergoing Chemotherapy: A Nationwide Retrospective Cohort Study in Japan. (13th May 2022) - Abe, Hiroaki; Sumitani, Masahiko; Matsui, Hiroki; Inoue, Reo; Konishi, Mitsuru; Fushimi, Kiyohide; Uchida, Kanji; Yasunaga, Hideo
Abstract : BACKGROUND: It is unclear whether gabapentinoids affect the development of delirium. We aimed to determine the association between gabapentinoid use and hyperactive delirium in older cancer patients undergoing chemotherapy. METHODS: We conducted propensity score-matched analyses using data from a nationwide inpatient database in Japan. We included cancer patients with pain ≥70 years of age undergoing chemotherapy between April 2016 and March 2018. Patients receiving gabapentinoids were matched with control patients using propensity scores. The primary outcome was occurrence of hyperactive delirium during hospitalization, and the secondary outcomes were length of hospital stay, in-hospital fractures, and in-hospital mortality. Hyperactive delirium was identified by antipsychotic use or discharge diagnoses from the International Classification of Diseases, 10th Revision. RESULTS: Among 143, 132 identified patients (59% men; mean age, 76.3 years), 14, 174 (9.9%) received gabapentinoids and 128, 958 (90.1%) did not (control group). After one-to-one propensity score matching, 14, 173 patients were included in each group. The occurrence of hyperactive delirium was significantly lower (5.2% vs 8.5%; difference in percent, −3.2% [95% confidence interval, −3.8 to −2.6]; odds ratio, 0.60 [0.54–0.66]; P < .001), the median length of hospital stay was significantly shorter (6 days [interquartile range, 3–15] vs 9 days [4–17]; subdistribution hazard ratio, 1.22 [1.19–1.25]; P < .001), and the occurrence of in-hospital mortality was significantly lower in the gabapentinoid group than in the control group (1.3% vs 1.8%; difference in percent, −0.6% [−0.9 to −0.3]; odds ratio, 0.69 [0.57–0.83]; P < .001). Gabapentinoid use was not significantly associated with the occurrence of in-hospital fractures (0.2% vs 0.2%; difference in percent, 0.0% [−0.1 to 0.1]; odds ratio, 1.07 [0.65–1.76]; P = .799). The results of sensitivity analyses using stabilized inverse probability of treatment weighting were consistent with the results of the propensity score-matched analyses. CONCLUSIONS: Our findings suggest that gabapentinoid use is associated with reduced hyperactive delirium in older cancer patients undergoing chemotherapy, with no evidence of an increase in the fracture rate, length of hospital stay, or in-hospital death.